Peningkatan Kapasitas Perangkat Desa tentang Sarana Prasarana di Karangawen Kabupaten Demak - Hani Purwanti; Ferry Firmawan; Purwanto Purwanto (Jurnal Pengabdian KOLABORATIF, 2025)
Brambang Village, Karangawen District, experienced damage to infrastructure due to flash floods, while village officials lacked the capacity and knowledge to manage it. The purpose of this community service program is to improve village officials' ability to manage infrastructure through field reviews and Forum Group Discussions (FGD). The exercises improved the village officials' understanding and proficiency in assessing the state of the infrastructure, preparing repair plans, and overcoming damage due to disasters. Awareness of the importance of community participation also increased. This program produced concrete recommendations for repairing damaged infrastructure and is expected to be followed up immediately. With this increased capacity, Brambang village officials can manage infrastructure more effectively, delivering long-term advantages for the local community's well-being. This Community Service Program has succeeded in achieving its goals and helping to raise the community of Karangawen's standard of living.